PVC-Membrane Potentiometric Electrochemical Sensor Based on 2-(4-Oxopentan-2-ylideneamino)isoindoline-1,3-dione for Selective Determination of Holmium(III) - Hassan Ali Zamani (E-Journal of Chemistry, 2011)
2-(4-Oxopentan-2-ylideneamino) isoindoline-1,3-dione (OID) was found to be a suitable neutral ionophore in the fabrication of a highly selective Ho3+ membrane sensor. The electrode has a near-Nernstian slope of 19.6±0.5 mV per decade with a wide concentration range between 1.0×10-6 and 1.0×10-2 mol/L in the pH range of 3.5–8.8, having a fast response time (∼5 s) and a detection limit of 5.8×10-7 mol/L. This electrode presented very good selectivity and sensitivity towards the Ho3+ ions over a wide variety of cations, including alkali, alkaline earth, transition and heavy metal ions. The practical utility of the electrode has been demonstrated by its use as an indicator electrode for the potentiometric titration of a Ho3+ solution with EDTA and for the determination of Ho3+ ions concentration in mixtures of two and three different ions.